Biased Random-Key Genetic Algorithm Applied to the Optimal Reconfiguration of Radial Distribution Systems - Vargas, Rommel [UNESP]; Romero, Ruben [UNESP]; Franco, John F. [UNESP]; IEEE (Ieee, 2018)
The optimal reconfiguration of radial Electrical Distribution Systems (EDSs) is a classical optimization problem that deals with the operation of the system and is of great interest to the electricity sector. Although there is a large number of approaches in the specialized literature to solve this problem, the solution of the reconfiguration problem for large-scale EDSs is still difficult. This paper proposes a method to solve the reconfiguration problem of EDSs that is based on the specialized metaheuristic Biased Random-Key Genetic Algorithm, which showed excellent performance on the solution of complex problems in operational research. Tests carried out using a wellknown EDS demonstrate the efficiency of the proposed method.
Keywords: Biased random-key genetic algorithm; electrical distribution systems; power losses; reconfiguration